Relationship of motions between the arm and the legs in the diving motion of soccer goalkeepers - Numazu, N.; Fujii, N. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to clarify the relationship between the hand movement of the goalkeeper (GK) and the velocity of center of gravity (CG) in diving motion towards various heights and distances. Three male university GKs dived towards the shot. Three male university forward players performed instep kicking to twelve shot areas by forward dribbling. Three-dimensional (3D) coordinates of the body landmarks and ground reaction forces were obtained with a 3D motion capture system and two force platforms. The novel findings in this study were summarized as follows: (1) GKs changed not only the height of their CG but also the motions of their trunk and arm according to the shot heights; (2) exerting elbow joint torques is important for GKs to dive towards the near upper and near middle places; and (3) it is assumed that not only accelerating the CG but also the trunk and arm motions are necessary for the evaluation of diving skills for GKs.